Ups and downs for bananas - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Banana exports from the Windward Islands declined by 4,000 tonnes over the first quarter of 2001: 12,358 tonnes were exported compared with 17,876 tonnes for the first quarter of 2000. The decline can be largely attributed to St Lucia, whose banana...